Microsoft Outlook for Mac 2011 step by step - Langer, Maria (O'Reilly, 2011)
"Experience learning made easy--and quickly teach yourself how to organize your email. arrange your calendar, and manage tasks using Outlook on your Mac ..."--Page 4 of cover